400 Investigation of a translational astrocyte-targeted AAV-mediated gene addition therapy in two models of Vanishing White Matter disease - Jessica A. Herstine; Pi-Kai Chang; Sergiy Chornyy; Tamara J. Stevenson; Jessica Rediger; Julia Wentz; Nettie Pyne; Joshua L. Bonkowsky; Allison M. Bradbury (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: Vanishing White Matter Disease (VWM), is a childhood neurodegenerative leukodystrophy that presents with motor deficits, neurologic decline, and seizures leading to death.There are no treatments. Herein we investigate adeno-associated virus serotype 9 (AAV9) gene addition therapy for VWM. METHODS/STUDY POPULATION: To serve as a baseline for disease correction, we characterized the severe VWM Eif2b5I98M murine model with clinically relevant readouts including motor function, gait mapping and myelin loss through magnetic resonance imaging (MRI). Molecular characterization through the identification of biomarkers was also investigated. To provide targeted disease correction, we designed four gene replacement constructs to drive the rapeutic EIF2B5 expression in astrocytes—a critical cell type for VWM pathology. We are currently evaluating our AAV vectors in two murine VWM models, Eif2b5R191H and Eif2b5I98M, and are monitoring disease progression using traditional and clinically relevant readouts. RESULTS/ANTICIPATED RESULTS: The I98M mice display significant mobility loss, ataxic gait, and demyelination. Molecular characterization also indicates that the integrated stress response is significantly dysregulated, supporting the classic VWM phenotype. Our previous biodistribution study confirmed our ability to efficiently target astrocytes using varying iterations—including one novel—of the glial fibrillary acidic protein (GFAP) promoter. Our data suggests that targeting astrocytes with gene addition delays disease onset, partially rescues motor function, and attenuates myelin loss. Survival of the AAV9-gfaABC(1)D-EIF2B5 treated I98M mice is also significantly increased (p<0.0001), currently with a 2-fold extension in life expectancy. DISCUSSION/SIGNIFICANCE: Overall, we anticipate emergence of a lead astrocyte-targeted gene therapy candidate in which the data will be strengthened through the evaluation of clinically relevant measures in two murine models of disease, allowing fortimely translation to the clinic.